Turn of the Month Effect in Nepalese Stock Market: During and After COVID-19 Period - Rijal, Sumedha; Varal, Vinayak; Lath, Devansh; Phaiju, Isha (New Perspective: Journal of Business and Economics, 2025)
This research investigates the Turn of the Month (TOM) effect in the Nepalese stock market by comparing stock returns, volatility, and trading volume on TOM days versus Non-TOM days. The study also examines the TOM effect during and after the COVID-19 pandemic using secondary data from Nepse Alpha. Employing quantitative methods and statistical analysis through Python, results show that the TOM effect did not significantly impact stock returns in either period. However, stock return volatility was significantly higher during TOM days in the COVID-19 period, likely due to increased market uncertainty and unusual trading behaviors during the pandemic. This volatility spike disappeared after COVID-19, indicating the TOM effect was temporary and situational rather than systematic. Trading volume showed no significant changes across both periods. The study concludes that the TOM effect does not have a persistent influence on stock returns, volatility, or trading volume in Nepal’s market. The temporary volatility during COVID-19 is attributed to external shocks and does not persist in the normal market environment. These findings suggest that investors and market managers in Nepal should focus on fundamental, data-driven strategies instead of relying on calendar-based anomalies.